Crise da esquerda comunista: políticas do PCI e do PCP sobre a união europeia - Maia, Rodrigo Ismael Francisco [UNESP] (2015)
This thesis aims to understand the relationships between the Italian Communist Party (PCI) and the Portuguese Communist Party (PCP) about the European integration process which culminated in the EU, highlighting the connection between domestic and foreign policy in strategies of the parties. In Italy and Portugal, the establishment of the democratic system was part of the strategy of the two PCs, which had broad-based in the working class. The stagnation of the selforganization of the working classes and the end of social unrest processes have led to democratic normality and the internationalization of economies, liberalizing them. The PCI, promoting their particular Italian via to socialism, collaborated with the formation of the European Economic Community (EEC), the PCP that initially refused, began to take it as a source of benefits in defense of democracy. The EEC's social development was uneven and combined, in which countries became part of the common market at the same time the fragmentation ravaged the world of work. The isolation was a first defeat of the two PCs in national governments, and the other was the impossibility to move forward with the strategy of reforms toward socialism. To the practical and ideological failure was joined the politics at the threshold of execution of the EU, in front of the terminal crisis of the international communist left, when the PCI decided for dismantle and the PCP to the orthodox continuation.